Education for All: Strengthening Social Behaviours of Students in Diversity and Inclusion-Based School - Mewangi, Adila Bunga; Masrukhi, Masrukhi; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2024)
The diversity in Indonesia necessitates educators to create an environment accommodating this diversity in schools. This goal aligns with making education a means for